The effect of addition of a wettable biochar on soil water repellency. (November 2015) - Hallin, I. L.; Douglas, P.; Doerr, S. H.; Bryant, R.
Summary: The potential of biochar to ameliorate soil water repellency has not been widely studied. Previous studies have focused on the potential for biochar to induce or exacerbate existing water repellency rather than alleviate it. This study investigates the effect of adding wettable biochar to water‐repellent soil by comparing the water drop penetration times (WDPTs) of a control and biochar‐amended soil. The potential of wettable biochar to act as a physical amendment to water‐repellent soil was evaluated by mixing coarsely‐ground biochar (CGB, particle size range 250–2000 µm) or finely‐ground biochar (FGB, particle size range < 250 µm) with one strongly and one severely naturally water‐repellent soil in various quantities, and then measuring the WDPT for each mixture. When biochar particles did not fall within the size range of existing soil particles, an initial increase in both mean WDPT (WDPTM ) and variation in WDPT was observed with small additions of biochar. These effects possibly result from increased surface roughness and inhibition of infiltration by the suspension of drops above the average soil–air interface at a few hydrophobic points. Both CGB and FGB reduced soil water repellency, FGB more effectively than CGB. The addition of 10% w/w FGB reduced soil WDPT by 50%, and 25% FGB eliminated repellency. Direct absorption of water by biochar and an increase in soil surface area in contact with water are the predominant physical mechanisms involved. This exploratory study suggests biochar has the potential to amend water‐repellent soil.